Frailty as a dysruption of steroid “syncrinology” in elderly man - Valenti, Giorgio (Acta Biomedica Atenei Parmensis, 2007)
In the background of the endocrinological hypothesis of aging, frailty in man can be seen as a dysruption of syncrinology, a term with which we could define the harmonized activity of steroid hormones (DHEAS, cortisol, testosterone). Such endocrine age-related modifications might promote the activation of sarcopenia, which exerts a core position in the progression of frailty in the elderly. Consequently, the use of replacement treatment in order to delay the beginning of such steroid derangement might be a suitable strategy to improve the quality of life of man, whose life length has been significantly extended.